2020
DOI: 10.1055/s-0040-1709363
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Traumatic Brain Injury Due to Traffic Accidents in Latin America: A Narrative Review

Abstract: Objective Traumatic brain injuries (TBIs) are devastating injuries and represent a major cause of morbidity and mortality worldwide. Traffic accidents are one of the main causes, especially in low- and middle-income countries. The epidemiology of TBI due to road traffic in Latin America is not clearly documented. Methods A narrative review was conducted using PubMed, SCOPUS, and Google Scholar, looking for TBI studies in Latin America published between 2000 and 2018. Seventeen studies were found that met the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 15 publications
0
28
0
8
Order By: Relevance
“…It has been shown that in lowmiddle income countries in the past 17 years, violence and road traffic accidents (RTAs) have been the main causes of TBI and have associated high mortality (13) . Similarly, Dunne et al (14) revealed that, RTA is a common cause of TBI in Latin America. They demonstrated that, TBI due to RTAs is more frequent in males between the ages of 15 and 35 years, and patients in motor vehicles accounted for most cases, followed by pedestrians, motorcyclists, and cyclists.…”
Section: Discussionmentioning
confidence: 91%
“…It has been shown that in lowmiddle income countries in the past 17 years, violence and road traffic accidents (RTAs) have been the main causes of TBI and have associated high mortality (13) . Similarly, Dunne et al (14) revealed that, RTA is a common cause of TBI in Latin America. They demonstrated that, TBI due to RTAs is more frequent in males between the ages of 15 and 35 years, and patients in motor vehicles accounted for most cases, followed by pedestrians, motorcyclists, and cyclists.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies reported that head injury was found to be most common injuries during traffic accidents (34) ,being 42.1% making a substantial contribution to RTA cases (35) , the main reasons of the fatality is severe traumatic brain injury (TBI) produced by head dullpowers (36,37) . In low-and middle-income countries 43% of individuals with TBI that cause by cars accidents (39) . Although numerous studies have been done, the consequence of skull fracture on TBIs has not been obviously assumed (14) .…”
Section: Discussionmentioning
confidence: 99%
“…Dunne J et al in their narrative review concluded that males have a higher tendency of getting involved in traumatic outcomes as they found a higher prevalence of males (77%) in their compilation of eight studies on RTAs. 23 On the other hand, females are believed to be more prone to fall from balconies, rooftops, and stairs.…”
Section: Discussionmentioning
confidence: 99%